Effects of covid-19 on the cost of construction enterprises: Case of China - Wu, Fei; Wang, Bo; Lim, Thien Sang (Faculty of Business, Economics and Accountancy, 2021)
Covid-19 epidemic has caused huge losses to the world economy, and its development speed and impact have far exceeded expectations. The outbreak of the epidemic is mainly concentrated in densely populated areas such as urban centers. Construction enterprises are labor-intensive enterprises, and the risk of increased costs is inevitable. This paper takes Chinese construction enterprises as an example, based on the survey report issued by the China Construction Industry Association on the impact of the Covid-19 epidemic on construction enterprises, analyzes the impact of the Covid-19 epidemic on the cost of construction enterprises, and provide relevant suggestions for how to deal with the risks of increased costs for construction enterprises.